Eugenia and Kazimierz Stołyhwo as anthropologists - Jasicki, Bronisław (Anthropological Review, 1978)
At the tenth anniversary of death of the two outstanding Polish physical anthropologists Professor Kazimierz Stołyhwo and Professor Eugenia Stołyhwo the author presents their scientific work against historical background of anthropology in Poland. In the present article contribution of the two scientists to accomplishments of physical anthropology is described along with their role in formation of anthropological centre at Kraków.